EFL STUDENTS' PERSPECTIVES ON USING ChatGPT IN WRITING - Nur Salsabila; Warsidi; Sulviana (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2026)
This study aims to explore EFL students’ perspectives on the use of ChatGPT in writing tasks. The research employs a qualitative descriptive method, with data collected through questionnaires and semi-structured interviews. The participants consisted of undergraduate students from the English Education Department, who actively engaged with ChatGPT to support their academic writing. The findings reveal two main aspects: 1) Perceived Usefulness, where students acknowledged that ChatGPT helps them generate ideas, improve vocabulary, and enhance sentence structures and Perceived Ease of Use, as most students found the platform accessible, user-friendly, and supportive in completing writing tasks; and 2) Challenges, which include issues such as Information Literacy, Reproduction Literacy and Socio-Emotional Literacy. Overall, students demonstrated positive perceptions of ChatGPT as a supplementary tool in their writing process. However, they also encountered challenges in managing information, reproducing content, and dealing with socio-emotional aspects. Therefore, teacher guidance and students’ critical evaluation are still essential to ensure effective and responsible use of ChatGPT in academic writing.